The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ldr.1132
|View full text |Cite
|
Sign up to set email alerts
|

Soil Property Changes Following Irrigation With Coalbed Natural Gas Water: Role of Water Treatments, Soil Amendments and Land Suitability

Abstract: Saline‐sodic water is a by‐product of coalbed natural gas (CBNG) production in the Powder River Basin of Wyoming, USA and is being beneficially used in places as irrigation water. This study evaluated effects of 2 years of natural precipitation on soil properties of a hay field after the cessation of managed irrigation with CBNG water. The hay field had been irrigated with only CBNG water [CBNG(NT)], CBNG water amended with gypsum [CBNG(G)] or gypsum plus sulfur via a sulfur burner [CBNG(GSB)] in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
(79 reference statements)
2
17
0
Order By: Relevance
“…3). There is limited research on effects of S burner on soil chemistry, and available literature indicated that similar to the current study, application of S burner‐treated water increased the infiltration rate that resulted in reduced EC e and sodicity, especially in surface soils (Johnston et al, 2013). However, the maximum salinity and sodicity observed after 1 yr of irrigation with S burner‐treated (blended) water were still above the threshold.…”
Section: Resultssupporting
confidence: 76%
“…3). There is limited research on effects of S burner on soil chemistry, and available literature indicated that similar to the current study, application of S burner‐treated water increased the infiltration rate that resulted in reduced EC e and sodicity, especially in surface soils (Johnston et al, 2013). However, the maximum salinity and sodicity observed after 1 yr of irrigation with S burner‐treated (blended) water were still above the threshold.…”
Section: Resultssupporting
confidence: 76%
“…Although sodicity (SAR) increased in the upper 45 cm, which covers the effective root zone of switchgrass in this study, the values were less than the sodic threshold of 13. However, even in the deeper depth (45–60 cm) soils that exceeded the threshold, no impairment in soil permeability was observed due to higher EC e values that helped to keep electrolyte concentration in the soil solution above the threshold electrolyte concentration (Johnston, Vance, & Ganjegunte, ). Toward the end of the study, solubilization and redistribution of native calcium minerals (calcite and gypsum) resulted in lowering of pH (G. Ganjegunte et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last years, numerous studies have indicated that restoration needs to recover soil functionality, and this call is taking place all over the world (Ahmad et al, 2013;Johnston et al, 2013;Mao et al, 2014;Moreno et al, 2014;Novara et al, 2014;Roy and McDonald, 2015;Sacristán et al, 2015;Sadeghi et al, 2015;Srivastava et al, 2014). Some authors indicate that this task should be accomplished with a broad view by considering how soils can interfere with human health (Brevik and Sauer, 2015).…”
Section: N Seco-reigosa Et Al: Adsorption Desorption and Fractionamentioning
confidence: 99%